Functional outcome of column specific fixation in the management of complex tibial plateau fractures - Thapa, Bishwamber; Sitoula, Prakash; Jha, Ranjib; Thapa, Santosh (Birat Journal of Health Sciences, 2022)
Introduction: Complex tibial plateau fractures usually have complicated intra-articular fracture pattern, often associated with severe soft tissue injury and high risk of wound complications. Single or dual column plating fixation principle based upon conventional x-ray for such fractures may not address multiplanar comminution that  often has posterior shearing or  coronal fractures. Computed tomography based evaluation of such fractures  and column specific  approach allow direct fracture visualization and anatomic reduction  that results in satisfactory outcome.Objectives: To assess the clinical and functional outcome and complications of complex tibial plateau fractures fixed with column specific fixation principle.Methodology: This prospective study was carried out from September 2019 to August 2021 in Orthopaedic department of Nobel Medical College, Biratnagar. Consecutive sampling was used among patient with complex tibial plateau fractures meeting the inclusion criteria. Among 30 patients, with  closed and Gustilo grade I or II Schatzker type V-VI fractures or AO type-C injuries to the proximal tibia were operated on column specific approach and followed up for clinico-radiological evaluation.Results: In this study, most of the patients belonged to 31-40 years of age group with mean age of 40.47 years. Majority of patients were male( 76.7%). Fracture was highly associated with road traffic accident which accounted for 83%. Fourteen patients underwent anteromedial and anterolateral plating(46.67%), 10 patients underwent anterolateral and posteromedial plating(33.33%) and remaining 6 patients underwent triple column plating(20%). The Rasmussen’s functional score at final follow up was  27.17±2.793(range 21-30). 86.7% patients had acceptable clinical outcome. The mean Rasmussen’s radiological score at final follow up was 8.97±1.217(range 6-10). Thus 93.4% patients had acceptable radiological outcome.Conclusion: Column specific approach addresses all the fracture fragments of complex tibial plateau fractures to achieve acceptable clinical and radiological outcome.